3D printing of multi-material composites with tunable shape memory behavior. (August 2020) - Yuan, Chao; Wang, Fangfang; Qi, Biyun; Ding, Zhen; Rosen, David W.; Ge, Qi
Abstract: Three-dimensional (3D) printing has offered considerable convenience in fabricating functional structures constructed with shape memory polymers (SMPs). Conventionally, to meet the specific requirements for given applications, the shape memory property of a SMP is regulated by tailoring its molecular structure from the perspective of polymer chemistry. By virtue of the recent advances in multi-material 3D printing technology, new opportunities have emerged to customize the shape memory property from the perspective of composite material design. In this work, we propose a novel layout design strategy to 3D print multi-material composites incorporating heat-responsive SMP and flexible elastomer. Under a given volume ratio of SMP and elastomer, distinct shape memory performances are obtained for different material layouts. The underlying mechanisms are theoretically investigated based on the mechanics of composite materials and finite element (FE) simulations are conducted to provide quantitative predictions for the experimental results. As a demonstration, composites of different material layouts are used as building blocks to fabricate bilayer laminates where the incompatibility of shape fixity are pre-embedded to trigger the programmed active bending. Graphical abstract: Unlabelled Image Highlights: A layout design strategy is proposed to regulate the shape memory performance of multi-material composites. Theoretical analysis and finite element simulations are conducted to investigate the tunable shape memory performance. Composites of different material layouts are laminated into bilayer structures to achieve programmed active bending.